Correlação entre citomegalovirose, perfil imunológico de risco (PIR) e mortalidade em idosos - Caldeira,Marcelo Henrique Reis (2011)
Human cytomegalovirus (HCMV) is associated with important cause of morbidity and mortality in immunocompromised individuals, but their action in immunocompetent individuals has gained prominence in the field of geriatrics, in immunosenescence's works, with numerous studies revealing a significant association between HCMV chronic infection and increase of functional limitations and mortality in the population after 60 years. Research has demonstrated that HCMV chronic infection is directly related to immunological changes of aging, specifically with changes in lymphocyte T cell response, this set of changes was called immune risk profile (IRP), which is associated with the limitation on the ability of the immune system to organize an effective response to pathogenic microorganisms, resulting in increased susceptibility to infections, among other consequences. This article aims to review the role of HCMV in the aging, the immune risk profile markers and their consequences for the health of elderly population.